Impacts of selected pesticides on parthenium beetle, Zygogramma bicolorata pallister under laboratory conditions in Sri Lanka - Halangoda, H.R.; Pakeerathan, K.; Mikunthan, G. (Sabaragamuwa University of Sri Lanka, 2022)
Parthenium (Parthenium hysterophorus L.) is one of the Asteraceae family's most vicious herbaceous weeds. It emerged as the most significant invasive weed of the planet and has invaded 98 countries representing all the continents. Presence of toxic phytochemicals and allelochemicals like parthenon and coronopilin in Parthenium causes severe yield loss on economically important crops as well as poses threat to biodiversity, human and animal health. Among the management practices, chemical, physical, regulatory, fire, mycoherbicides, agronomic practices, competitive displacement, and traditional biological control are the options available for managing parthenium (Dhileepan et al., 2009). Manual and chemical weed control are effective in agricultural fields to control parthenium, but not cost-effective in pastures, vast natural areas, or wastelands. By implementing an integrated pest management practices involving multiple tactics n combination can effectively control Parthenium weed (Dhileepan et al., 2009). Parthenium beetle (Zygogramma bicolorata) is found to be a safe biocontrol agent, and its effectiveness has proven in many countries.